Pulmonary embolism secondary to inappropriate use of oral contraceptive therapy: A case report (2016)
Forty-one year old female admitted to the hospital because of symptoms and signs suggestive of pulmonary thromboembolism which was confirmed by CT angiography. There was no history of prior thromboembolic events, smoking, venous stasis or vascular lesion (negative lupus anticoagulant and anticardiolipins). The only documented hypercoagulability factor was the use of an oral contraceptive containing drospirenone and ethinylestradiol for the last year. The patient was treated with anticoagulants such as enoxaparin and she recovered without sequelae; she is currently under treatment with warfarin as an outpatient. It is known that the use of combined oral contraceptives in patients over 35 years old requires caution, largely due to higher risk of thromboembolic events associated with increased hepatic synthesis of several coagulation factors. Therefore, this case represents a potentially fatal and preventable severe adverse reaction. © 2016, Editorial Ciencias Medicas. All rights reserved.